Efficacy and safety evaluation of rivaroxaban vs. warfarin among non-valvular atrial fibrillation patients undergoing lower extremity revascularization - Yu, Qingyuan; Chen, Cheng; Xu, Jinyan; Xiao, Yu; Bao, Junmin; Yuan, Liangxi (Frontiers in Cardiovascular Medicine, 2022)
Introduction The efficacy and safety of antithrombotic strategies remain uncertain in patients with atrial fibrillation undergoing lower-extremity revascularisation. Materials and methods Between January 2011 and November 2021, 319 patients with atrial fibrillation after lower-extremity revascularisation received rivaroxaban or warfarin treatment as anticoagulation regimens with different antiplatelet therapy strategies. The primary efficacy outcome was the composite of acute limb ischaemia, major amputation for vascular causes, myocardial infarction, ischaemic stroke, clinically driven target lesion revascularisation, and death from vascular causes. The safety outcomes were major bleeding events according to the International Society on Thrombosis and Haemostasis classification criteria. Results A total of 178 and 141 patients received rivaroxaban and warfarin treatments, respectively, after revascularisation with or without antiplatelet regimens. The incidence of the primary efficacy outcome at 36 months in the rivaroxaban group (44 patients, 24.7%) tended to be lower than that in the warfarin group (43 patients, 30.5%) (hazard ratio, 0.870; 95% confidence interval, 0.565–1.339; P = 0.527). The incidence of the secondary efficacy outcomes decreased in the rivaroxaban group (56 patients, 31.6%) compared with that in the warfarin group (61 patients, 43.2%). Major bleeding events occurred in three patients (1.7%) in the rivaroxaban group and five patients (3.5%) in the warfarin group; no significant difference in fatal or intracranial bleeding was observed between the groups. Conclusion This study describes practical experience regarding the use of rivaroxaban and warfarin in patients with peripheral arterial disease complicated by non-valvular atrial fibrillation following endovascular intervention. The efficacy and safety outcomes do not differ significantly between rivaroxaban and warfarin.